1999
DOI: 10.1029/1999ja900094
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic oscillations due to filamentary structures in the magnetic‐field‐aligned flow: The ion‐acoustic branch

Abstract: Abstract. Recent space missions such as FAST and Freja report highly structured plasma flows along the magnetic field. Electrostatic fluctuations that can be supported by such inhomogeneous parallel flows are investigated. It is found that even a small transverse gradient in parallel flow can significantly reduce the critical value of the relative ion-electron field-aligned drift for the current-driven electrostatic ion acoustic modes. It is also shown that the shear-modified ion acoustic mode can be excited w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 71 publications
1
57
0
Order By: Relevance
“…On the basis of theoretical studies about current instabilities in the magnetosphere for a homogenous plasma (Kindel and Kennel, 1971), current thresholds are too high, and these mechanisms may not operate over a broad altitude range. For an inhomogenous plasma, if sheared flows are present, as it is likely in the auroral region, the thresholds are significantly lower (Gavrishchaka et al, 1999(Gavrishchaka et al, , 2000. In these latter works, the instability mechanism has been described in a local limit and has been successfully applied only to observations in the nightside upward current region by FAST at an altitude of 4 000 km.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of theoretical studies about current instabilities in the magnetosphere for a homogenous plasma (Kindel and Kennel, 1971), current thresholds are too high, and these mechanisms may not operate over a broad altitude range. For an inhomogenous plasma, if sheared flows are present, as it is likely in the auroral region, the thresholds are significantly lower (Gavrishchaka et al, 1999(Gavrishchaka et al, , 2000. In these latter works, the instability mechanism has been described in a local limit and has been successfully applied only to observations in the nightside upward current region by FAST at an altitude of 4 000 km.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why emissions with k || >k ⊥ occur only in short bursts, and why waves with k || <k ⊥ may exist in longer bursts and are more common. We note that in an inhomogeneous plasma, including, for example, a varying particle drift along the geomagnetic field, IA waves may also exist for other temperature ratios (Ganguli et al, 2002 andGavrishchaka et al, 1999). Different directions of the k-vector correspond to different wave modes, assigned different names, but there is no sharp theoretical limit between the different modes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of transverse shears in FA ion drifts on electrostatic IA instability eigenmodes and threshold conditions was studied by Gavrishchaka et al (1998) and Gavrishchaka et al (1999). In particular, they suggested that velocity shears can significantly lower the threshold current of the current-driven electrostatic ion-acoustic (CDEIA) instability, even when T i ∼ T e .…”
Section: Introductionmentioning
confidence: 99%
“…Later, Perron et al (2009) systematically studied the threshold solutions of St-Maurice et al (2007) kinetic dispersion relation for different ion to electron temperature ratios. Besides, the Gavrishchaka et al (1998) and Gavrishchaka et al (1999) work was extended by Spangler et al (2002) who derived a dispersion relation for a Maxwellian plasma which includes temperature anisotropy and shears. They showed that ion temperature anisotropy alters the frequency modes of the sheared CDEIA instability by solving numerically the dispersion equation.…”
Section: Introductionmentioning
confidence: 99%